EFEKTIVITAS PELAKSANAAN MEDIASI PERKARA PERCERAIAN DI PENGADILAN AGAMA BEKASI - Adityo, Rayno Dwi; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This study aims to know on the effectiveness of mediation Implementation ofdivorce in Religious Court of Bekasi. This research used field Research and qualitativeapproach. Primary data source that is result of interview and observation at BekasiReligious Court. Secondary data is derived from book literature, print media andelectronic media. conclusion of this research that the implementation of divorce mediationin the Religious Court of Bekasi is as follows: pre-mediation, mediation, mediation report,trial continued mediation report. Factors supporting the success of the mediation processare, the ability of a good mediator, the willingness of the parties litigation to reconcile,and the child of the plaintiff and the defendant's marriage. While the constraints are asfollows: the parties (the plaintiff and the defendant) will not make peace, the duration oftime is relatively short, the facilities are not adequate, and the difficulty of the disputedcase. Therefore the effectiveness of the implementation of mediation of divorce dependson the presence and absence of factors supporting and inhibiting earlier.